NBD-Based Environment-Sensitive Fluorescent Probes for the Human Ether-a-Go-Go–Related Gene Potassium Channel - Li, Qi; Chai, Lijuan; Dong, Gaopan; Zhang, Xiaomeng; Du, Lupei (Frontiers in Molecular Biosciences, 2021)
Three environment-sensitive probes were developed for the hERG channel based on the nitrobenzoxadiazole fluorophore herein. After careful evaluation, probes M1 and M3 were found to have a high affinity for imaging the hERG channel in the cell-based experiment. Compared with other fluorescent labeling technologies (such as fluorescent proteins), these probes afford a convenient and economical method to determine hERG channel in vitro and in cellulo. Therefore, these probes are expected to be applicable for usage in physiological and pathological studies of hERG channels and have the potential to establish a screening system for hERG channels.